Five new minute orb-weaving spiders of the family Mysmenidae from China (Araneae) - Lin, Yucheng; Li, Shuqiang (Zootaxa, 2013)
Five new mysmenid species are described from Southwest China including Mosu dayan n. sp. (male and female), Mosu tanjia n. sp. (male and female), Mysmena baoxingensis n. sp. (male and female), Mysmenella yinae n. sp. (male and fe-male), Trogloneta uncata n. sp. (male). Males of the genus Mosu are described for the first time. All new species are from caves or leaf litter. Morphological illustrations and photos of all new species are given.